1999
DOI: 10.1002/(sici)1099-0488(19990415)37:8<769::aid-polb3>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based hydrogels: A new polymer-based system with excellent laser-damage threshold properties

Abstract: Two types of chitosan hydrogel systems have been prepared that have a laser damage threshold (LDT) up to 35 times higher than commercial PMMA bulk materials. For these samples, the LDT increases with increasing water content. The mechanism of laser damage and the contribution of water to their high laser damage resistance have been examined. DSC measurements indicate water within the hydrogels exist in various states, each with different laser damage resistance properties. These various states play a key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Many attempts have been made to improve the laser damage resistance of polymer materials in the last two decades [11][12][13]. Recently, our lab reported that hydrogel systems based on chitosan polymers have emerged as a new class of host materials for laser applications [14,15]. These chitosan hydrogel systems show excellent laser damage thresholds (LDT) of 290-450 mJ, 20 to 35 times higher than that of commercial PMMA (16 mJ).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Many attempts have been made to improve the laser damage resistance of polymer materials in the last two decades [11][12][13]. Recently, our lab reported that hydrogel systems based on chitosan polymers have emerged as a new class of host materials for laser applications [14,15]. These chitosan hydrogel systems show excellent laser damage thresholds (LDT) of 290-450 mJ, 20 to 35 times higher than that of commercial PMMA (16 mJ).…”
Section: Introductionmentioning
confidence: 55%
“…Different temperature and frequency sweeps were performed in an attempt to further understand the relationship between the structure and properties. These results are compared to the conclusions made in our recent studies using DSC measurements [15] with regard to the high LDT observed.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations